What are patients and carers looking for in the OSCE?. (18th May 2020) - Symons, Jools; Edwards, Kim; Henderson, Kay; Tate, Joannie
Abstract : Some medical schools work with patients and carers to help teach students how to make patients their first concern. Jools Symons and colleagues ask members of the University of Leeds Patient and Carer Community for their advice for students sitting Objective Structured Clinical Examinations (OSCEs)